(3JMaI GdCTQGa HeYQaI GdCWQGas - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3ef fYHO NjQ s
(3BNQgG (B:s
(3Edi (B: (3YQhI s
(3GdfSNI HgG MhGTs
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
Keywords: (3GdMOjK h GdeUWdMs